Functional Repair Assay for the Diagnosis of Constitutional Mismatch Repair Deficiency From Non-Neoplastic Tissue - Shuen, Andrew Y; Lanni, Stella; Panigrahi, Gagan B; Edwards, Melissa; Yu, Lisa; Campbell, Brittany B; Mandel, Ariane; Zhang, Cindy; Zhukova, Nataliya; Alharbi, Musa; Bernstein, Mark; Bowers, Daniel C; et al. (Journal of clinical oncology, 2019)
PURPOSE: Constitutional mismatch repair deficiency (CMMRD) is a highly penetrant cancer predisposition syndrome caused by biallelic mutations in mismatch repair (MMR) genes. As several cancer syndromes are clinically similar, accurate diagnosis is critical to cancer screening and treatment. As genetic diagnosis is confounded by 15 or more pseudogenes and variants of uncertain significance, a robust diagnostic assay is urgently needed. We sought to determine whether an assay that directly measures MMR activity could accurately diagnose CMMRD. PATIENTS AND METHODS: In vitro MMR activity was quantified using a 3'-nicked G-T mismatched DNA substrate, which requires MSH2-MSH6 and MLH1-PMS2 for repair. We quantified MMR activity from 20 Epstein-Barr virus-transformed lymphoblastoid cell lines from patients with confirmed CMMRD. We also tested 20 lymphoblastoid cell lines from patients who were suspected for CMMRD. We also characterized MMR activity from patients with neurofibromatosis type 1, Li-Fraumeni syndrome, polymerase proofreading-associated cancer syndrome, and Lynch syndrome. RESULTS: All CMMRD cell lines had low MMR activity (n = 20; mean, 4.14 ± 1.56%) relative to controls (n = 6; mean, 44.00 ± 8.65%; P < .001). Repair was restored by complementation with the missing protein, which confirmed MMR deficiency. All cases of patients with suspected CMMRD were accurately diagnosed. Individuals with Lynch syndrome (n = 28), neurofibromatosis type 1 (n = 5), Li-Fraumeni syndrome (n = 5), and polymerase proofreading-associated cancer syndrome (n = 3) had MMR activity that was comparable to controls. To accelerate testing, we measured MMR activity directly from fresh lymphocytes, which yielded results in 8 days. CONCLUSION: On the basis of the current data set, the in vitro G-T repair assay was able to diagnose CMMRD with 100% specificity and sensitivity. Rapid diagnosis before surgery in non-neoplastic tissues could speed proper therapeutic management.
Keywords: MutS Homolog 2 Protein; nádorové biomarkery; Colorectal Neoplasms; Biomarkers, Tumor; prediktivní hodnota testů; DNA vazebné proteiny; Cell Line, Tumor; homolog 2 proteinu MutS; Phenotype; DNA Mismatch Repair; nádorové buněčné linie; Predictive Value of Tests; Case-Control Studies; nádory mozku; Mutation; fenotyp; kolorektální nádory; Humans; genetická predispozice k nemoci; DNA Repair Enzymes; Mismatch Repair Endonuclease PMS2; Genetic Testing; Neoplastic Syndromes, Hereditary; Brain Neoplasms; oprava chybného párování bází DNA; lidé; mutace; Genetic Predisposition to Disease; studie případů a kontrol; enzymy opravy DNA; mismatch repair endonukleáza PMS2; dědičné nádorové syndromy; DNA-Binding Proteins; genetické testování; MutL Protein Homolog 1; MutL homolog 1